Optically Active Polyoxometalate‐Based Silica Nanohelices: Induced Chirality from Inorganic Nanohelices to Achiral POM Clusters. Issue 44 (23rd July 2018) - Attoui, Mariam; Pouget, Emilie; Oda, Reiko; Talaga, David; Le Bourdon, Gwénaëlle; Buffeteau, Thierry; Nlate, Sylvain
Abstract: In order to investigate the principle of chiral induction from nanometric silica helices to polyoxometalate (POM) clusters, a series of optically active silica POM‐based nanohelices (NANOPOMs) have been prepared by electrostatic grafting and direct adsorption of α‐Keggin polyoxometalate [α‐PW12 O40 ] 3− to well‐defined left‐ and right‐handed silica nanohelices. UV/Vis, Raman, DRIFT, TEM, HR‐TEM, EDS and circular dichroism (CD) spectroscopy were used to characterize these NANOPOMs, and confirm the presence of POM clusters as well as their interactions with the helical support. The optical activity of the left‐handed and right‐handed NANOPOMs has been proven by CD spectroscopy. Their CD spectra are mirror images of one another, showing cotton effects at around 214 and 276 nm, this last contribution corresponding to the oxygen‐to‐tungsten charge‐transfer bands of Keggin polyoxoanions. The CD signal of POM clusters is strongly enhanced for NANOPOMs built by adsorption of POM onto silica nanohelices, indicating a better induced optical activity to POM clusters. These nanohelices are stable, recoverable and active catalysts in the oxidation of sulfides. To the best of our knowledge, the present research represents the first examples of optically active POM‐containing silica nanohelices in which achiral POM clusters have been grafted onto silica nanohelices, and display chiroptical effects. Abstract : Silica NANOPOM helices : Left‐ and right‐handed silica NANOPOM helices have been prepared by electrostatic and direct adsorption of α‐Keggin polyoxometalate to silica nanohelices. The presence of POM clusters and their interactions with the helical template are confirmed by various characterization techniques. The induced chirality from silica nanohelices to POM clusters is evidenced by CD spectroscopy. These NANOPOM helices are robust and easy to handle.